Progress in mine safety science and engineering II : proceedings of the 2nd International Symposium of Mine Safety Science and Engineering, Beijing, China, 21-23 September 2013 /: proceedings of the 2nd International Symposium of Mine Safety Science and Engineering, Beijing, China, 21-23 September 2013. ([2014]) - Unknown
No abstract available